Using the principles of the sharing economy as a method of increasing the efficiency of the enterprise in the post-war period - Maryna Mavrina; Mykola Belopolskiy (Економічний вісник університету, 2023)
Relevance of the research topic. Today, a big problem for enterprises is a significant decrease in demand for their products. The main reason for this is the destruction of critical infrastructure because of hostilities, high rates of inflation, a decrease in the real income of the population, and a humanitarian disaster in the south and east of the country. Formulation of the problem. Using, for example, diversification as a method of increasing the efficiency of production and sales of products is no longer enough. It is necessary to look for and use new tools to protect enterprises from declining sales. The purpose of the article is to apply the principle of rational consumption to ensure the efficiency of the enterprise in the post-war period. Results of the article. It was determined that the principle of rational consumption together with the use of technological solutions of subscription systems open wide prospects for domestic enterprises. After all, using the principles of the sharing economy will make it possible to modernize business processes in such a way that enterprises can provide their services hundreds of times cheaper than before and at the same time be profitable, significantly expand their geography and create long-term financial relations with their consumers. Field of application of results. The conclusions of the article can be used mainly at enterprises in the sphere of wholesale and retail trade, manufacturing. Conclusions. The activity of enterprises in the field of trade and production is accompanied by certain difficulties. Sales of non-essential goods will decrease in the coming years. To prevent the bankruptcy of enterprises that do not belong to industries that provide basic human needs, the managers of these enterprises can introduce the principles of the sharing economy to create attractive, and most importantly, affordable and mutually beneficial conditions for cooperation with target customers. These principles can be applied both in the B2B (business to business) and B2C (business to consumers) sectors.